Prospects for the Development of Small Hotels in Modern Conditions - NIKOLSKAYA, Elena Yurievna; PASKO, Olga Vladimirovna; USPENSKAYA, Marina Evgenjevna; LYSOIVANENKO, Elena Nikolaevna; PINKOVSKAYA, Galina Viktorovna (Journal of Environmental Management and Tourism, 2020)
The paper is dedicated to justifying the prospects for the development of small hotels in modern conditions. It has been found that the Russian Federation demonstrates an example of the rapid development of small hotel business. In some of the country’s regions, progressive trends can be observed, which are associated with an increase in the capacity of the hotel industry related to the attraction of small-sized accommodation facilities to this area. It has been revealed that Saint Petersburg is the undisputed leader in promoting small hotel business. It has been determined that Moscow is another significant representative of the developing small hotel market. Despite an insignificant share of small hotels in the total amount, it is small hotels in Moscow that make up the majority of the newly introduced key count. However, this cannot physically significantly affect the ratio of rooms per thousand capita, which is too low in Moscow.